Conceptualizing hard and soft benefits of adopting BIM in construction projects: A systematic review - Tohfa, T. S.; Farouk, Abdelrahman M.; Rahimi, A. Rahman (Springer, 2024)
Building information modeling (BIM) has been emphasized in modern construction management as it provides several benefits for project completion. Extensive study is required for a deeper understanding of benefit realization, precisely the hard and soft benefits of BIM. Several works have been undertaken to explore the benefits of adopting BIM. However, these works cannot differentiate between the hard and soft benefits of BIM adoption. This study aims to analyze the trends in research articles that identified the hard and soft benefits of adopting BIM. To achieve this aim, 17 articles were selected for a systematic literature review (SLR) using the recommended reporting items for systematic reviews and meta-analyses (PRISMA) technique. The findings showed the hard benefits include conflict management, quality, cost control, data management, and innovation. In contrast, the soft benefits include collaboration and communication, productivity and efficiency, project performance, improved information management, and sustainability. It is worth emphasizing that this is one of the earliest studies that conceptualizes the soft and hard benefits of BIM adoption. Hence, it is expected to be one of the foundations for future research in this area.